Does orbital angular momentum have effect on laser's scattering by molecular atmosphere?. (November 2018) - Sun, Wenbo; Hu, Yongxiang; Weimer, Carl; Hou, Weilin; Lee, Tsengdar; Videen, Gorden; Baize, Rosemary R.
Highlights: Scattering of laser with orbital angular momentum (OAM) by small particles is studied. The 3D CPML FDTD technique is applied in the solution of OAM laser beam scattering. The OAM has no effect on laser's scattering by molecular atmosphere. Abstract: Lasers with orbital angular momentum (OAM) have potential applications in communication technology, manipulation of particles, and remote sensing. Because of its unusual light-scattering properties, the OAM laser's interaction with a molecular atmosphere must be studied to ensure that it is not lossy for communication or remote-sensing applications that involve its transmission through an atmospheric environment. In this study, the finite-difference time-domain (FDTD) method [21] is applied to calculate the light scattering of the purely azimuthal (the radial mode number is assumed to be zero) Laguerre–Gaussian (LG) beams with OAM by very small dielectric particles. Not like Lorenz-Mie solutions, the FDTD method can calculate for particles off the central axis of the LG beam. It is found that when the particles are very small, and the topological charge number of the OAM of a laser is not extremely large, the laser's OAM has little effect on the scattering phase function. This suggests that Rayleigh theory can be applied directly to calculate the light scattering by atmospheric molecules. The transmission of a laser beam with OAM in a molecular atmosphere is not different from that of a regular Gaussian beam.